Agrarian Law in the Field of Land After Regional Autonomy - Damianus Krismantoro (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This research will be carried out to see how land law exists in Indonesia after the implementation of regional autonomy. The central government’s efforts to grant autonomy to local or district governments after the reforms are implemented are aimed at providing fast and appropriate services to the community concerning land affairs. This research will be carried out by conducting a document study on autonomy in the land sector, which then impacts agrarian law. This study found that the Basic Regulations on Agrarian Principles have the principle of authority in the land sector, which has a centralized nature and must change by itself. Local governments need to be able to provide good services in the land sector in the current era of regional autonomy.